Dr Rodney D Cooke: new Director of CTA - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
CTA's newly-appointed Director Dr Rodney D Cooke, who is from Britain, took up his duties on a continuing basis in August. Two months earlier he had joined the Centre to participate in the 1995 annual Advisory Committee meeting and the subsequent...